LATE POSTOPERATIVE COMPLICATIONS OF NECROTIZING ENTEROCOLITIS IN CHILDREN AND THEIR PREVENTION MEASURES (Herald of the National Children's Medical Center, 2025)
Necrotizing enterocolitis (NEC) is one of the most severe and frequently encountered gastrointestinal (GI) diseases in newborns and premature infants. The incidence is 1–5 per 1,000 live births, with 80–90% of cases occurring in premature infants and those with low birth weight (
Keywords: necrotizing enterocolitis; premature infants; surgical complications; postoperative outcomes; intestinal stenosis; rehabilitation